Knowledge, attitude, and perception of mothers towards emergency management of dental trauma in Salem district, Tamil Nadu: A questionnaire study - Kruthika Murali; Ramesh Krishnan; V Suresh Kumar; Shankar Shanmugam; Prakash Rajasundharam (Wolters Kluwer Medknow Publications, 2014)
Background: Dental trauma is one of the main oral health problems in childhood, and can cause pain and distress. It is important to provide emergency care to combat the aftermaths of trauma. Aim: The aim of the study is to assess the knowledge and attitude of mothers regarding dental trauma and its management. Materials and Methods: A questionnaire consisting of 33 closed-ended questions were used to interview 150 mothers who participated in the study. The questions assessed the knowledge and attitude of mothers towards their child's dental visit, dental trauma, and its management. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) version 17.0. Results: Mother's previous experience of dental trauma when associated with the preservation of avulsed tooth of the child, those mothers who had the experience of dental trauma reported that they would discard the tooth which was found to be statistically significant (P < 0.05) when compared to the mothers with no experience of trauma. The education status of the study population when associated with the knowledge variables of avulsion, it was found that most of the variables had statistically significant association with P < 0.05. Conclusion: This study reveals that there is a lack of awareness among the mothers regarding the emergency management of dental trauma. This warrants the need of an effective communication between dental professionals and mothers for better handling of dental emergencies.